Readiness As A Microfoundational Approach To Knowledge Management - Samara, Khalid (Journal of Knowledge Management Practice, 2013)
Over the years, many theories have noted that the core factor that acts as a barrier to successful knowledge management (KM) initiatives is attributable, in part, to the individual’s lack of readiness to change. However, a significant gap in the literature is the lack of empirical and conceptual support to the idea that KM is inherently a change effort affecting issues of how to enact change in individuals. More recent work, have highlighted that one of the reasons for this gap in the knowledge literature, is that majority of studies as a whole are usually pre-occupied with macro-level constructs stemming from forces at the organisational level. We argue that readiness-for change is an important step towards understanding the micro processes of individual actions and interactions, because research in this area examines how change occurs from the individual’s perspective. Based on the literature, we present a model to help us explore the micro processes of organisational KM initiatives. Within this model, we build on previous work of Foss (2007) explanation of microfoundations and fuse it with insights of Armenakis and Harris (2002) theory of readiness for individual change. A discussion is presented demonstrating future directions towards a microfoundational approach to KM.
Keywords: knowledge management; Readiness-for change; Microfoundations; Organisational change